Agua potable un derecho de la humanidad: características fisicoquímicas, bacterias y metales pesados - Castillo, Eveling (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research carried out at the National University of the Altiplano, whose objective was to determine the physicochemical, bacteriological quality, content of heavy metals and to propose alternative solutions for water in the city of Ilave (Puno, Peru). Methodology: Take samples from the catchment point, pump deposit and reservoir according to standardized sampling standards, pH was determined using the electrometric method, hardness using the titrametric method, chlorides using the Mohr method, sulfates, nitrites and nitrates by absorption spectrophotometry, total dissolved solids by conductimetry, bacteria by the most probable number and heavy metals by atomic absorption spectrophotometry, all of them carried out in the DIRESA Laboratory - Puno (Peru), the parameters were contrasted with the established in the D.S. 004 - 2017 of the MINAM. Results: pH between 8.05 and 794 units, hardness between 174.62 and 160.67 mg/l of CaCO3, chlorides between 143.61 and 111.72 mg/l, sulfates between 69.54 and 56.36 mg/l, nitrites between 0.96 and 0.53 mg/l, total dissolved solids between 428.27 and 367.23 mg/l, turbidity between 5.17 and 3.87 NTU, all within the established ranges of the water quality standards, except at the catchment point, where the turbidity and the CT count exceed the standards, the load bacterial between 46 MPN/100 ml and 23 MPN/100 ml; the metal content is below that indicated in the standards, except for lead ions with 0.0842 mg/l. Solution alternative: filter with activated carbon impregnated with chitosan, the process of boiling and subsequent sedimentation of the water, use of modified zeolitic minerals, electrocoagulation, two bucket method and removal assisted by sunlight. Conclusion: Ilave's drinking water complies with current regulations regarding physicochemical parameters, meanwhile it has lead above what is established.